Methodology of nondestructive identification of defective concrete zones in unilaterally accessible massive members - Gorzelańczyk, Tomasz; Hoła, Jerzy; Sadowski, Łukasz; Schabowicz, Krzysztof (Journal of Civil Engineering and Management, 2013)
The paper deals with the nondestructive identification of defective concrete zones in unilaterally accessible massive members, for example, access galleries in hydroelectric power plants. The concrete in such zones is, for various reasons, excessively porous. The authors propose to use state-of-the-art acoustic testing techniques, including ultrasonic tomography, integratively to detect and identify defective zones. An original methodology for such tests has been developed. The methodology is illustrated with an example of its practical application to a real civil engineering structure.First published online: 24 Oct 2013